Conceptualizing and Reimagining the Future of Inclusive Education in the UAE - Meda Lawrence; Efthymiou Efthymia; AlHammadi Muna; Williams Cara; Fteiha Mohamed (De Gruyter, 2023)
The current study explored how students in various universities across the United Arab Emirates (UAE) conceptualized inclusive education and views of the future with participation from twenty-one pre-service teachers from different universities within the UAE. Data collection consisted of an open-ended questionnaire and semi-structured interviews analyzed using a qualitative case study within an interpretive paradigm. Results indicated that students unanimously conceptualized inclusion from a holistic point of view and projected the future to be associated with a higher level of differentiated instruction. However, the conditions of the Education Act and the results were not in agreement with the premise of liberation pedagogy, as students with special needs reverted to a passive state and adopted a dependent relationship with the teacher. In conclusion, teachers' motivation was faith in humanity, the rejection of fatalism, and the belief that all learners can actively participate in the transformation of the world by participating in liberation pedagogy, which caters to the diverse needs of students in present and future environments.